Metabolite Profiling of Dihydroartemisinin in Blood of Plasmodium-Infected and Healthy Mice Using UPLC-Q-TOF-MSE - Zhao, Yifan; Sun, Peng; Ma, Yue; Chang, Xiaoqiang; Chen, Xingyu; Ji, Xin; Bai, Yue; Zhang, Dong; Yang, Lan (Frontiers in Pharmacology, 2021)
Dihydroartemisinin (DHA) and its’ derivatives have been employed as the most powerful first-line drugs for malarial treatment for several decades. The metabolism of DHA has not been studied clearly. Previous reports were focused on the pharmacokinetics procedure of DHA in healthy rat. The metabolites of DHA in red blood cells (RBC) especially in the RBC from Plasmodium infected models have rarely studied. While, the Plasmodium species parasitize inside RBC, and these cells should be the final place where DHA performs its activity. In this study, the profile of DHA metabolites in bio-sample (blood, plasma, RBC) of infected and healthy mouse were investigated with UPLC QTOF MS and UNIFI platform to obtain insight into DHA metabolism. Results show that a total of 25 (30) metabolites successfully were identified in infected (healthy) blood, 27 (27) in infected (healthy) plasma, and 15 (22) in infected (healthy) RBC. Results show that hydroxylation, OH-dehydration, and glucuronidation reactions were found to be important in the metabolic pathway in vivo. Significantly, DHA metabolites inside RBC were identified for the first time. 8-hydroxy (8-OH) DHA, 4α-OH deoxy ART, and 6β-OH deoxy ART were identified in vivo for the first time.